Full-length transcriptional analysis reveals the complex relationship of leaves and roots in responses to cold-drought combined stress in common vetch - Min, Xueyang; Wang, Qiuxia; Wei, Zhenwu; Liu, Zhipeng; Liu, Wenxian (Frontiers in Plant Science, 2022)
Plant responses to single or combined abiotic stresses between aboveground and underground parts are complex and require crosstalk signalling pathways. In this study, we explored the transcriptome data of common vetch (Vicia sativa L.) subjected to cold and drought stress between leaves and roots via meta-analysis to identify the hub abiotic stress-responsive genes. A total of 4,836 and 3,103 differentially expressed genes (DEGs) were identified in the leaves and roots, respectively. Transcriptome analysis results showed that the set of stress-responsive DEGs to concurrent stress is distinct from single stress, indicating a specialized and unique response to combined stresses in common vetch. Gene Ontology (GO) enrichment analyses identified that “Photosystem II”, “Defence response” and “Sucrose synthase/metabolic activity” were the most significantly enriched categories in leaves, roots, and both tissues, respectively. The Kyoto Encyclopedia of Genes and Genomes (KEGG) enrichment analysis results indicated that “ABC transporters” are the most enriched pathway and that all of the genes were upregulated in roots. Furthermore, 29 co-induced DEGs were identified as hub genes based on the consensus expression profile module of single and co-occurrence stress analysis. In transgenic yeast, the overexpression of three cross-stress tolerance candidate genes increased yeast tolerance to cold-drought combined stress. The elucidation of the combined stress-responsive network in common vetch to better parse the complex regulation of abiotic responses in plants facilitates more adequate legume forage breeding for combined stress tolerance.